2014
DOI: 10.1080/15205436.2013.835424
|View full text |Cite
|
Sign up to set email alerts
|

Need for Orientation, Selective Exposure, and Attribute Agenda-Setting Effects

Abstract: This study explores the ability of an interaction between need for orientation (NFO) and selective exposure to explain citizen's motivations to seek information from specific media sources and the consequences of this behavior for attribute agenda-setting effects. It draws important conceptual distinctions between the two moderate NFO categories, distinguishing active involvement NFO (high relevance and low uncertainty) from passive involvement NFO (low relevance and high uncertainty). The results suggest that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(28 citation statements)
references
References 41 publications
0
24
0
4
Order By: Relevance
“…In the first case, there should be a high need for orientation, while in the second and third cases the indicator is moderate, and in the latter case it is low. However, the studies have shown that groups with a moderate need for orientation are not the same and behave in relation to information in different ways (Camaj 2014). By proposing such a classification, D. Weaver supports the idea that the specificity of the media audience and its motives can be taken into account when forecasting and explaining media effects (Blumler 1979).…”
Section: Agenda-setting Theorymentioning
confidence: 95%
“…In the first case, there should be a high need for orientation, while in the second and third cases the indicator is moderate, and in the latter case it is low. However, the studies have shown that groups with a moderate need for orientation are not the same and behave in relation to information in different ways (Camaj 2014). By proposing such a classification, D. Weaver supports the idea that the specificity of the media audience and its motives can be taken into account when forecasting and explaining media effects (Blumler 1979).…”
Section: Agenda-setting Theorymentioning
confidence: 95%
“…Integra dos componentes importantes: la relevancia y la incertidumbre (McCombs, 2006;McCombs y Stroud, 2014), una clasificación realizada en función de su medición específica. En la realización de estudios empíricos sobre este factor (Kim, 2013;Camaj, 2014) es importante analizar en el público los temas que resultan puntos no tratados por los medios, o que se destacan por su relevancia como tema. Luego debe determinarse por qué razón se escoge ese tema: por desconocimiento o por interés en él.…”
Section: Condiciones Contingentes En El Establecimiento De La Agendaunclassified
“…Este elemento ha sido valorado a partir del interés que se da hacia la política (Casermeiro, 2004;Camaj, 2014), en gran medida porque existe un repositorio bastante extenso que se orienta hacia esa dirección investigativa.…”
Section: Condiciones Contingentes En El Establecimiento De La Agendaunclassified
“…• La necesidad de orientación, como resultado de la relevancia que los asuntos públicos adquieren, de los vacíos cognitivos que se generan en el proceso de comprensión social de la realidad y del interés de las personas en saciarlos (Matthes, 2006;Kim, 2013;Camaj, 2014).…”
Section: Marco Teóricounclassified